Apocynin influence on oxidative stress and cardiac remodeling of spontaneously hypertensive rats with diabetes mellitus. Issue 1 (December 2016) - Rosa, C.; Gimenes, R.; Campos, D.; Guirado, G.; Gimenes, C.; Fernandes, A.; Cicogna, A.; Queiroz, R.; Falcão-Pires, I.; Miranda-Silva, D.; Rodrigues, P.; Laurindo, F.; et al.
Abstract Purpose Although increased oxidative stress is a major component of diabetic hypertensive cardiomyopathy, research into the effects of antioxidants on cardiac remodeling remains scarce. The actions of antioxidant apocynin include inhibiting reactive oxygen species (ROS) generation by nicotinamide adenine dinucleotide phosphate (NADPH) oxidases and ROS scavenging. We evaluated the effects of apocynin on cardiac remodeling in spontaneously hypertensive rats (SHR) with diabetes mellitus (DM). Methods Male SHR were divided into four groups: control (SHR, n = 16); SHR treated with apocynin (SHR-APO; 16 mg/kg/day, added to drinking water; n = 16); diabetic SHR (SHR-DM, n = 13); and SHR-DM treated with apocynin (SHR-DM-APO, n = 14), for eight weeks. DM was induced by streptozotocin (40 mg/kg, single dose). Statistical analyzes: ANOVA and Tukey or Mann–Whitney. Results Echocardiogram in diabetic groups showed higher left ventricular and left atrium diameters indexed for body weight, and higher isovolumetric relaxation time than normoglycemic rats; systolic function did not differ between groups. Isolated papillary muscle showed impaired contractile and relaxation function in diabetic groups. Developed tension was lower in SHR-APO than SHR. Myocardial hydroxyproline concentration was higher in SHR-DM than SHR, interstitial collagen fraction was higher in SHR-DM-APO than SHR-APO, and type III collagen protein expression was lower in SHR-DM and SHR-DM-APO than their controls. Type I collagen and lysyl oxidase expression did not differ between groups. Apocynin did not change collagen tissue. Myocardial lipid hydroperoxide concentration was higher in SHR-DM than SHR and SHR-DM-APO. Glutathione peroxidase activity was lower and catalase higher in SHR-DM than SHR. Apocynin attenuated antioxidant enzyme activity changes in SHR-DM-APO. Advanced glycation end-products and NADPH oxidase activity did not differ between groups. Conclusion Apocynin reduces oxidative stress independently of NADPH oxidase activity and does not change ventricular or myocardial function in spontaneously hypertensive rats with diabetes mellitus. The apocynin-induced myocardial functional impairment in SHR shows that apocynin actions need to be clarified during sustained chronic pressure overload.